Low-complexity direct computation algorithm for cubic-spline interpolation scheme - Hong, Shao-Hua; Wang, Lin; Truong, Trieu-Kien (Journal of visual communication and image representation, 2018)
•We make some comments on the direct computation algorithm for CSI scheme developed by Lin et al.•A low-complexity direct computation algorithm for CSI scheme is developed to improve the computational efficiency.•Extensive experiments performed on some standard gray images demonstrate that such a low-complexity direct computation CSI scheme can achieve almost the same objective and subjective performances with approximately 32% fewer arithmetic operations in comparison with the direct computation CSI scheme.•This considerately modified version of the direct computation CSI scheme can be implemented by the use of the pipeline structure and is naturally suitable for VLSI implementations. Cubic-spline interpolation (CSI) scheme is known to be designed to resample the discrete image data based on the least-square method in conjunction with the cubic convolution interpolation (CCI) function. It is superior in performance and can be used together with the discrete cosine transform (DCT)-based image or video codec to improve the coding performance for a variety of high compression ratios. In this paper, we firstly make some comments on the direct computation algorithm for CSI scheme developed by Lin et al. Moreover, a low-complexity direct computation algorithm for CSI scheme is developed to further improve the computational efficiency. The mathematical derivations and simulation results indicate that such simplified CSI scheme using the proposed low-complexity direct computation algorithm can achieve almost the same objective and subjective performance with much fewer arithmetic operations in comparison with the CSI scheme using the direct computation algorithm.